Electron diffraction characterization of nanocrystalline materials using a Rietveld‐based approach. Part II. Application to microstructural analysis. Issue 6 (27th October 2022) - Sinha, Ankur; Ischia, Gloria; Lutterotti, Luca; Gialanella, Stefano
Abstract : Quantitative microstructural characterization of different nanocrystalline materials based on Rietveld refinement of electron diffraction patterns is presented to demonstrate the application of the methodology described in Part I [Sinha et al. (2022). J. Appl. Cryst. 55, 953–965 ]. Abstract : This is the second in a two‐paper series concerning the quantitative characterization of nanocrystalline materials using an electron‐diffraction‐based approach, in which a full‐pattern fitting Rietveld‐based refinement is applied to electron powder diffraction data in transmission electron microscopy (TEM). Part I [Sinha et al. (2022). J. Appl. Cryst. 55, 953–965 ] established a standard calibration protocol to determine the instrumental effects, with special emphasis on the camera length and the diameter of the selected area apertures. Possible application cases are now considered to demonstrate the capabilities of the approach, including the evaluation of the phase composition of TEM specimens, an operation that reveals new application fields for this powerful materials characterization technique. In this regard, different types of material specimen are examined: nanocrystalline yttrium oxide, silicon, titanium dioxide and debris from disc brake wear, each one featuring specific aspects to be tackled with the proposed methodology. To demonstrate the limits of the proposed approach as concerns the material characteristics, an analysis of a hematite sample obtained from the heat treatment of natural goethite, displaying a relatively coarse crystallite size, is performed and a critical discussion of the results is given.